Twins - Johnson, Varian (Graphix, 2020)
Maureen and Francine Carter are twins and best friends. They enjoy the same foods, participate in the same clubs, and are partners whenever there's a school project. But on the first day of sixth grade, Francine wants to be called "Fran" and she makes a point of trying to be different from Maureen: joining the chorus, dressing differently, and only having two classes with her sister. But when both girls run for class president, their relationship becomes even more strained and Maureen begins to wonder if sisters really are forever.